Policy Advice between Ambition and Reality - Armin Steinbach (Wirtschaftsdienst)
Abstract Evidence-based policy remains an unfulfilled ambition given political constraints. On one hand, academic policy advice is widely acknowledged as indispensable, with policymakers stressing the relevance of external policy advice for policy formulation. On other hand, the impact of policy advice remains limited for a variety of reasons. This contribution discusses the variable conditions under which policy advise can be effective, notably its function to compensate for a lack of expertise, lack of resources in ministries and parliament as well as the degree of politicisation of a given policy field.